1998
DOI: 10.1099/0022-1317-79-10-2405
|View full text |Cite
|
Sign up to set email alerts
|

The Semliki Forest virus vector induces p53-independent apoptosis.

Abstract: Three deletion mutants of the structural protein region of the Semliki Forest virus (SFV) genome, including one which encompassed all the viral structural protein genes, induced apoptosis in BHK cells at 48 h after transfection, as shown by DNA laddering and TUNEL staining, as did the wild-type SFV4 RNA. A similar result was obtained for the SFV1 expression vector, which has a multicloning site inserted in place of the structural protein genes. However, in cells transfected with viral RNA containing a deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0
3

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 26 publications
0
79
0
3
Order By: Relevance
“…SFV vectors have an inherent p53-independent apoptosis inducing capability, 6 which has been successfully used to treat tumours in nude mice, 7,37 and it is likely that this operates also for the vectors used in this study. However, the presence of the enhancer in rSFV10-E-IL12 is unlikely to increase this inherent apoptosis induction since all cells infected by the unenhanced vector undergo apoptosis and the vector does not spread intercellularly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SFV vectors have an inherent p53-independent apoptosis inducing capability, 6 which has been successfully used to treat tumours in nude mice, 7,37 and it is likely that this operates also for the vectors used in this study. However, the presence of the enhancer in rSFV10-E-IL12 is unlikely to increase this inherent apoptosis induction since all cells infected by the unenhanced vector undergo apoptosis and the vector does not spread intercellularly.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of the enhancer in rSFV10-E-IL12 is unlikely to increase this inherent apoptosis induction since all cells infected by the unenhanced vector undergo apoptosis and the vector does not spread intercellularly. 6,7,37 The enhanced ability of this vector to destroy tumour cells must therefore result from the induction of enhanced IL-12 secretion. IL-12 has a potent proinflammatory activity that may contribute to the antitumour effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection of cells does not proceed beyond a single round and the infected cells die by apoptosis. 29 The transient nature of infection with recombinant SFV thus provides an important safety advantage when considering using SFV as a vaccine in humans.…”
mentioning
confidence: 99%
“…9 It has also been shown that the induction of p53-independent apoptosis by the SFV vector is an inherent function of the vector RNA and not dependent on expression of cloned heterologous genes. 10 Targeting of alphavirus vectors has been shown to be feasible, although only 1 targeting strategy has so far been described for alphavirus vectors, based on coupling of a monoclonal antibody to a viral spike protein via a protein A sequence. 11 Other targeting strategies involving modification of the viral spike proteins may be feasible, as has been described for adenovirus vectors.…”
mentioning
confidence: 99%